EL DESARROLLO DE LA MIPYME Y LA VINCULACION UNIVERSITARIA EN PUERTO VALLARTA, JALISCO - Manuel Ernesto Becerra Bizarrón; Elba Martina Cortes Palacios; Luis Ignacio Zuñiga Bobadilla; Nora Luz Alegría García (European Scientific Journal, ESJ, 2014)
The university has permeated linking multiple contexts, as well as educational, business and labor, is considered the links between universities, enterprises and other actors such as the government. This linkage is an important way of job training and business building. The idea of these ties with the company has evolved, so that today is conceived not only to understand the needs of production companies, but as the association strength to the best and fullest fulfillment of economic and social purposes (Ducci 2013). The Univa Squad Vallarta, operates the university PROVEMUS consulting program in partnership with Fojal And COECYTJAL, which primarily aims to increase the competitiveness of SMEs in Puerto Vallarta by strengthening their management. The program began operation in 2007, 148 companies have been addressed with the participation of 466 students and 22 consultants until 2011. This research presents an analysis of the strengthening of SMEs reached under PROVEMUS attended university outreach program. The work is not experimental or ex post facto, a transactional descriptive design.